Self-hydrolyzing maleimides improve the stability and pharmacological properties of antibody-drug conjugates - Lyon, Robert P; Setter, Jocelyn R; Bovee, Tim D; Doronina, Svetlana O; Hunter, Joshua H; Anderson, Martha E; Balasubramanian, Cindy L; Duniho, Steven M; Leiske, Chris I; Li, Fu; Senter, Peter D (Nature biotechnology, 2014)
A new method for linking antibodies to drugs produces conjugates with improved stability and efficacy. Many antibody-drug conjugates (ADCs) are unstable in vivo because they are formed from maleimide-containing components conjugated to reactive thiols. These thiosuccinimide linkages undergo two competing reactions in plasma: elimination of the maleimide through a retro-Michael reaction, which results in loss of drug-linker from the ADC, and hydrolysis of the thiosuccinimide ring, which results in a derivative that is resistant to the elimination reaction. In an effort to create linker technologies with improved stability characteristics, we used diaminopropionic acid (DPR) to prepare a drug-linker incorporating a basic amino group adjacent to the maleimide, positioned to provide intramolecular catalysis of thiosuccinimide ring hydrolysis. This basic group induces the thiosuccinimide to undergo rapid hydrolysis at neutral pH and room temperature. Once hydrolyzed, the drug-linker is no longer subject to maleimide elimination reactions, preventing nonspecific deconjugation. In vivo studies demonstrate that the increased stability characteristics can lead to improved ADC antitumor activity and reduced neutropenia.